Sequential average segmented microscopy for high signal-to-noise ratio motion-artifact-free in vivo heart imaging - Vinegoni, Claudio; Lee, Sungon; Fumene Feruglio, Paolo; Marzola, Pasquina; Nahrendorf, Matthias; Weissleder, Ralph (OPTICAL SOC AMER, 2013)
In vivo imaging is often severely compromised by cardiovascular and respiratory motion. Highly successful motion compensation techniques have been developed for clinical imaging (e.g. magnetic resonance imaging) but the use of more advanced techniques for intravital microscopy is largely unexplored. Here, we implement a sequential cardiorespiratory gating scheme (SCG) for averaged microscopy. We show that SCG is very efficient in eliminating motion artifacts, is highly practical, enables high signal-to-noise ratio (SNR) in vivo imaging, and yields large field of views. The technique is particularly useful for high-speed data acquisition or for imaging scenarios where the fluorescence signal is not significantly above noise or background levels. (c) 2013 Optical Society of America